2008
DOI: 10.1002/jobm.200700161
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of endophytic bacteria which could be find in the apoplastic sap of the medullary parenchym of the stem of healthy sugarcane plants

Abstract: The genetic diversity of 29 endophytic bacterial strains isolated from apoplastic sap of the medullary parenchym of the stem of healthy sugarcane plants grown in Cuba was analysed by Two Primers-Ramdom Amplified Polymorphic DNA fingerprinting (TP-RAPD) and 16S rRNA gene sequencing. The strains were distributed into 17 groups on the basis of their TP-RAPD patterns, and a representative strain from each group was subjected to 16S rRNA gene sequencing. Analysis of these sequences showed that the isolates belong t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 36 publications
2
22
0
4
Order By: Relevance
“…Similar to the present study, Velázquez et al (2008) obtained endophytes from sugar cane that were phylogenetically very close to the following genera: Bacillus and Staphylococcus, from the Firmicutes group; Microbacterium, Micrococcus, and Kocuria from the Actinobacteria group; Rhizobium and Gluconacetobacter from the α-Proteobacteria group; Comamonas and Xanthomonas from the β-Proteobacteria group; and Acinetobacter and Pantoea from the γ-Proteobacteria group.…”
Section: Molecular Identification Of Isolates Based On Partial 16s Rdsupporting
confidence: 86%
“…Similar to the present study, Velázquez et al (2008) obtained endophytes from sugar cane that were phylogenetically very close to the following genera: Bacillus and Staphylococcus, from the Firmicutes group; Microbacterium, Micrococcus, and Kocuria from the Actinobacteria group; Rhizobium and Gluconacetobacter from the α-Proteobacteria group; Comamonas and Xanthomonas from the β-Proteobacteria group; and Acinetobacter and Pantoea from the γ-Proteobacteria group.…”
Section: Molecular Identification Of Isolates Based On Partial 16s Rdsupporting
confidence: 86%
“…Stamford et al (1998) identified the genus Staphylococcus as endophytic of yam bean. A similar phenomenon was observed by Velásquez et al (2008), who were also able to identify the genus Staphylococcus as being endophytic of sugar cane through the analysis of 16S rRNA. Vendan et al (2010) also identified endophytic bacteria from ginseng and observed that the genus Staphylococcus, confirm the results obtained in this study.…”
Section: Characterization Of Classical Taxonomysupporting
confidence: 79%
“…The nifH nucleotide sequences similar to those of Azonexus caeni and Rhodopseudomonas palustris were also similar to those of Zoogloea oryzae and Magnetospirillum magneticum, respectively. The genetic diversity of endophytic bacteria strains isolated from apoplastic sap of healthy sugarcane stems in Cuba showed a wide variety of phylogenetic groups (Velázquez et al 2008). Quantitative analysis of the diversity and population of actively N 2 -fixing endophytic bacteria should be advanced.…”
Section: Diversity Of Nifh Sequences By Dna Analysismentioning
confidence: 99%